ANALISIS TERHADAP PUTUSAN PENGADILAN PAJAK NOMOR PUT-000410.99/2024/PP/M.XVIB TAHUN 2024: STUDI KASUS SENGKETA PAJAK PT. SINAR PELITA ABADI - Malau, Imanuel Maruli Tua (Universitas Kapuas, 2025)
Tax disputes are often a complex issue in the Indonesian tax system, especially when it comes to the issuance of Tax Bills (STP). This research analyzes a tax dispute case between PT Sinar Pelita Abadi as the Plaintiff and the Directorate General of Taxes as the Defendant, related to STP on Income Tax (PPh) for the May 2022 tax period. This research uses a normative juridical method with a descriptive approach, data collection techniques through document studies, and qualitative data analysis. The results of the analysis show that the issuance of STP by the Directorate General of Taxes does not meet the formal and material requirements as stipulated in the applicable tax regulations. The Tax Court decided to grant PT SPA's lawsuit and cancel the STP. This finding emphasizes the importance of compliance with administrative and substantial procedures in the issuance of STP, as well as the role of the tax court in ensuring justice for taxpayers. In addition, this study also identifies the need for reforms in the tax system to improve transparency, accuracy, and accountability of tax authorities. By providing a comprehensive analysis of this case, this research contributes to the development of a fairer and more effective tax dispute resolution system in Indonesia.